Procedimento metodológico participativo e embasado em análise multicritério para avaliação de configurações de barramentos - Pereira, Andressa Christiane (2009)
The implantation of reservoirs for water supply induces a series of positive and negative impacts, such as social, cultural, economical, environmental, political, among others. The magnitude and extension of these impacts depend on the places where the reservoirs are implanted. The implantation is based, traditionally and predominantly, on technically specialized methodologies that little value the effective engagement of the main actors in the process of Environmental Impact Assessment (EIA) for each potential location. Such a process is mainly led by professionals/specialists linked to the consultancy company responsible for the development of the EIA Study, and to the authority in charge ofthe environmental licensing. Among the consequences of the adoption ofsuch non-participative methodologies, we can list: important EI indicators not being considered in the analyses in the context of a local / regional / global reality; but the use of less important indicators; deficient evaluation of the EI indicators due to the lack of diversity of positions and viewpoints related to the data valuation, which should integrate the multiplicity and diversity of actors and interests involved in it. We must mention that few are the scientific works about the effect ofdams from a point of view that combines multidisciplinary approach and social participation throughout its development. The purpose of the present work is to present a participatory methodology for ranking potential locations of dams, entitled “MPPAL + -CB”, as a support to the decision process about the implantation of this kind of enterprise, which, according to the principles of sustainable development, considers important aspects of the physical, biotical, economical, social, geographical and political dimensions, through a multicriterial analysis.The use of a multicriterial analysis is illustrated by means of a hypothetical simulation. Based on bibliographical analysis and assessment by experts, the proposedmethodological process is evaluated, which indicates to be a significant contribution to the subject in both scientific and technical ways. Finally, aiming at the relevancy of the cited methodological process for practical purposes, some comments / observations are presented.